Phytoaccumulation of heavy metals from contaminated soils by vetiver grass (Vetiveria zizanioides) in Malaysia / Ng Chuck Chuan - Ng , Chuck Chuan (2017)
A phytoremediation study was carried out to assess the capability of selected plant species to bio-accumulate contaminated heavy metals in soils. The relative soil- plant metal transfer coefficients such as biological concentration factor (BCF), bioaccumulation coefficient (BAC), translocation factor (TF) and percentage of metal uptake efficacy were employed to determine the mobility and potential phytoavailability of heavy metals in soil. Preliminary evaluation of potential tropical plant species with water spinach (I. aquatica), okra (A. esculentus), acacia (A. mangium), mucuna (M. bracteata), imperata (I. cylindrical), pennisetum (P. purpureum) and Vetiver (V. zizanioides) were conducted to assess the Cd, Cu, Pb and Zn accumulations with different levels of metal contamination in soils. Among these species, Vetiver grass was identified to be most promising due to its positive biological characteristics of fast growth, good tolerance to environmental stress, ability to withstand and bio-accumulate high levels of contaminated heavy metals in soils. Consequently, continuous phytoassessment of Vetiver grass with the application of higher levels of Cd and Pb concentrations were performed to evaluate its effectiveness for soil-plant metal accumulations. The threshold capability of heavy metals accumulation in Vetiver grass was found to be < 150 mg/kg for Cd and > 800 mg/kg for Pb, respectively. Under both single and mixed spiked heavy metals contamination in soils, Vetiver grass grown in mixed Cd+Pb, Cu+Zn and Cd+Pb+Cu+Zn spiked treatments accumulated higher heavy metal concentrations, specifically in the roots section than the single spiked treatments. With different types and composition levels of low cost soil amendments namely; ethylene-diamine-tetra-acetic acid (EDTA) disodium salt, elemental sulfur (S) and nitrogen (N) fertilizer; 25 mmol/kg EDTA and 300 mmol/kg N-fertilizer were found to be able to enhance the accumulation of both Cd and Pb in Vetiver grass. Phytoevaluation of Vetiver grass with EDTA soil amendment under both single and mixed enhanced heavy metals contaminated soils showed single Zn+EDTA enhanced treatment exhibited the highest Zn uptake whilst mixed Cd+Pb+EDTA, Cu+Zn+EDTA and Cd+Pb+Cu+Zn+EDTA enhanced treatments were tolerably effective to accumulate higher overall total concentration for Cd, Pb and Cu, respectively. It can be concluded that Vetiver grass is potentially the most viable plant species to be developed and used for phytoremediation, as both phytostabilizer and phytoextractor, in single and/or mixed heavy metals contaminated soils.